The use of diagnostic tools to assess the risks of chemicals to freshwater ecosystems: towards a unified evaluation framework - Andreu Rico; Udo Hommen; Beate I. Escher; Alina Koch; Anne Bado-Nilles; Belén González-Gaya; Enya Cody; Francisco Sylvester; Gabriele Treu; Gastón Alurralde; Henner Hollert; Iker Alvarez-Mora; et al. (Environmental Management, 2025)
The risk assessment of chemicals relies on multiple tools to quantify the ecological responses of ecosystems to existing chemical pollution. These tools are broadly categorized into three major groups: toxic pressure assessments, bioassays, and ecological monitoring. Here, we examine the strengths and limitations of these approaches, their current level of implementation for freshwater ecosystems across Europe, and their ability to evaluate the impacts of chemicals under field conditions. Additionally, we analyze the correspondence between results obtained from these tools when applied to a monitoring dataset from German streams. Our evaluation showed that no single tool can perfectly characterize the environmental impacts of chemical mixtures. However, each provides distinct lines of evidence, enabling the identification of chemicals driving ecological risks and the biological endpoints most likely to be affected, with ecological monitoring tools having the potential to show long-term ecosystem impairment. Finally, we propose recommendations to better understand the discrepancies between the outcomes of different methods and explore their potential integration into a unified water quality evaluation framework.